3(3u+2v)-3(4u-3v)=

Simple and best practice solution for 3(3u+2v)-3(4u-3v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3u+2v)-3(4u-3v)= equation:


Simplifying
3(3u + 2v) + -3(4u + -3v) = 0
(3u * 3 + 2v * 3) + -3(4u + -3v) = 0
(9u + 6v) + -3(4u + -3v) = 0
9u + 6v + (4u * -3 + -3v * -3) = 0
9u + 6v + (-12u + 9v) = 0

Reorder the terms:
9u + -12u + 6v + 9v = 0

Combine like terms: 9u + -12u = -3u
-3u + 6v + 9v = 0

Combine like terms: 6v + 9v = 15v
-3u + 15v = 0

Solving
-3u + 15v = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-15v' to each side of the equation.
-3u + 15v + -15v = 0 + -15v

Combine like terms: 15v + -15v = 0
-3u + 0 = 0 + -15v
-3u = 0 + -15v
Remove the zero:
-3u = -15v

Divide each side by '-3'.
u = 5v

Simplifying
u = 5v

See similar equations:

| 4x^2+29x+25=0 | | X^2-Y^2+15X-19Y-6=0 | | 4x^2-25x+19=-2x+4 | | -3x+5-2=x | | 10+10c=3c+3 | | 0=t^2-t-4 | | 3x-5y=-12solvey | | 10+10c=3c+c | | 3n^2-21=2n | | 22.9+3.00= | | 6x-20=3x+13 | | 2r^2-9r=-7 | | -5-t=21 | | 8=10+3x | | 2(2b+10)=12(b-1) | | 15x+8=20+3x | | 4(2x-2y)+5(2y-x)= | | S=2(3.14159)r^2+2(3.14159)rh | | x^2+6x+10=5 | | 9-9a= | | .75x=20 | | -5+3x=-14 | | (lnx+1)(lnx-1)=0 | | -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= | | 15x+2=6x+10 |

Equations solver categories